HIV Clinical Updates: New Single-Tablet Regimens. Issue 1 (January 2019) - Sebaaly, Jamielynn C.; Kelley, Denise
Objective: To review the pharmacokinetics, safety, common drug-drug interactions (DDIs), and advantages and disadvantages of new single-tablet regimens (STRs) approved since September 2016 for HIV-1 infection.Data Sources : A search using PubMed was conducted (2004 through May 2018) using the following keywords: single tablet regimen AND HIV . Additionally, a PubMed search was conducted for each individual STR using the generic names of the agents. For specific STRs, additional search terms were added to narrow results. Articles were evaluated for content, and additional references were identified from a review of literature citations. Conference abstracts from national and international HIV conferences were also searched.Study Selection and Data Extraction : Studies included were published randomized controlled trials and observational studies that evaluated STR approved since September 2016. Relevant conference abstracts were included if the study design was a randomized controlled trial or observational study pertaining to the STRs included.Data Synthesis : Four new STRs are available, including the first dual antiretroviral therapy (ART) regimen for virologically suppressed patients. Of the STRs, only 1 is a new molecular entity, and others include new combinations of existing agents that result in distinct advantages and disadvantages.Relevance to Patient Care and Clinical Practice : The treatment of HIV-1 continues to improve with new agents developed rapidly. These agents should be analyzed in regard to efficacy, safety, DDIs, and appropriateness for specific patients on an individual basis.Conclusions : STRs and agents in the pipeline continue to simplify ART regimens, increase medication adherence, and minimize toxicities.